Calcineurin Inhibitor–Free Mycophenolate Mofetil/Sirolimus Maintenance in Liver Transplantation: The Randomized Spare‐the‐Nephron Trial. Issue 7 (25th June 2013) - Teperman, Lewis; Moonka, Dilip; Sebastian, Anthony; Sher, Linda; Marotta, Paul; Marsh, Christopher; Koneru, Baburao; Goss, John; Preston, Dennis; Roberts, John P.; ,
<x xml:space="preserve">Abstract</x> Mycophenolate mofetil (MMF) and sirolimus (SRL) have been used for calcineurin inhibitor (CNI) minimization to reduce nephrotoxicity following liver transplantation. In this prospective, open‐label, multicenter study, patients undergoing transplantation from July 2005 to June 2007 who were maintained on MMF/CNI were randomized 4 to 12 weeks after transplantation to receive MMF/SRL (n = 148) or continue MMF/CNI (n = 145) and included in the intent‐to‐treat population. The primary efficacy endpoints were the mean percentage change in the calculated glomerular filtration rate (GFR) and a composite of biopsy‐proven acute rejection (BPAR), graft lost, death, and lost to follow‐up 12 months after transplantation. Patients were followed for a median of 519 days after randomization. MMF/SRL was associated with a significantly greater renal function improvement from baseline with a mean percentage change in GFR of 19.7 ± 40.6 (versus 1.2 ± 39.9 for MMF/CNI, P = 0.0012). The composite endpoint demonstrated the noninferiority of MMF/SRL versus MMF/CNI (16.4% versus 15.4%, 90% confidence interval = −7.1% to 9.0%). The incidence of BPAR was significantly greater with MMF/SRL (12.2%) versus MMF/CNI (4.1%, P = 0.02). Graft loss (including death) occurred in 3.4% of the MMF/SRL‐treated patients and in 8.3% of the MMF/CNI‐treated patients (P = 0.04). Malignancy‐related deaths were less frequent with MMF/SRL. Adverse events caused withdrawal for 34.2% of the MMF/SRL‐treated patients and for 24.1% of the MMF/CNI‐treated patients (P = 0.06). The use of MMF/SRL is an option for liver transplant recipients who can benefit from improved renal function but is associated with an increased risk of rejection (but not graft loss). Liver Transpl 19:675–689, 2013.. © 2013 AASLD.